Rhodium(II)-catalysed tandem aziridination and ring-opening: stereoselective synthesis of functionalised tetrahydrofurans. - Unsworth, W; Clark, N; Clark, N; Ronson, T; Ronson, T; Stevens, K; Stevens, K; Thompson, A; Thompson, A; Lamont, S; Lamont, S; Robertson, J; et al. (2014)
Aziridines formed upon treatment of allylic carbamates and homoallylic sulfamates with Rh(II) carboxylate catalysts under oxidative conditions are trapped by suitably-disposed hydroxyl groups to give functionalised tetrahydrofurans.